TREN ANGKA PARTISIPASI PENDIDIKAN SD DAN SMP DI KABUPATEN GUNUNGKIDUL - Rachmawati, Ani (Spektrum Analisis Kebijakan Pendidikan, 2021)
This research aims to: 1. Describe the trend in the enrollment rate of SD and SMP in Gunungkidul; 2. Describe the policies and programs that have been provided by the Gunungkidul Government to increase enrollment rates for elementary and junior high schools; 3. Describe the follow-up action of the Gunungkidul Government after seeing the trend of elementary and junior high school enrollment rates in Gunungkidul Regency. This research uses descriptive quantitative research with secondary data analysis which is equipped with interview method. Analysis of the data using trend analysis of the number of least squares with the type of linear model and the equation Y = a + bx. The results of this study are: 1. The trend of GER for SD and SMP in 2019-2028 in Gunungkidul tends to decrease; 2. Policies and programs of the Gunungkidul Government through PIP, scholarships and social assistance, compulsory education movement programs, retrieval programs, google for education, and education and training for educators; 3. The Gunungkidul government is following up on the results of the SD and SMP GER trends by validating data, continuing effective programs, and maximizing retrieval programs.Â Keywords: trends, gross participation rate, primary school, junior high school, gunungkidul regency.